Heterogeneity in price responsiveness for residential space heating in Germany - Hendrik Schmitz; Reinhard Madlener (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Space heating and hot water expenditures make up the majority of household energy demand in Germany, at 83.2%, making them an attractive target for energy policies. Using a panel dataset derived from yearly residential household surveys covering the years 1996 to 2014, we identify the determinants of heating expenditures for German households. We discover significant heterogeneity in expenditures depending on socioeconomic variables. For the full sample, we find a price elasticity of heating expenditures of 0.629. Elasticities vary significantly between individual groups, with values ranging from 0.523 to 0.716. Furthermore, a large number of technical and socio-demographic factors are significant in determining energy use. Our findings have implications for evaluating the effectiveness of policy measures that aim at influencing energy use across different groups of consumers.
Keywords: C23; D12; Q41; 330; Germany; Heating demand; Heating expenditures; Heterogeneity; Space heating